Upaya Pelestarian Kebudayaan Lokal Melalui Pembelajaran Berbasis Teknologi Di Sekolah Dasar - Muthi Luthfiyah, Hasna; Anggraeni Dewi, Dinie; Saeful Hayat, Rizky (Journal of Society and Development, 2022)
The purpose of this research is to analyze the importance of preserving local cultural values that are starting to disappear due to the negative impact of global technological developments. But in the same case that, with the development of this technology can be implemented towards preserving and maintaining local culture through the learning process in elementary schools. This research uses a qualitative approach with a literature study method. The results of this study found ways to utilize technology as an effort to maintain local culture in the learning process in elementary schools. The role of a teacher is very central in the world of education. Therefore, a teacher must be able to utilize technological advances as a learning medium, especially in learning cultural wealth. A teacher must be able to encourage the younger generation to preserve local culture. Because when a teacher is unable to provide an understanding of local culture, the younger generation will be eroded by globalization and the onslaught of western culture.